Analysis of Socio-Economic Characteristics Rice Farmers - roni jarlis (Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, 2022)
Abstract The aim is to determine the socio-economic characteristics of lowland rice farmers and the amount of income earned by lowland rice farmers in Nagari Pematang Panjang. The method used in this research is the case study method. The data collected in this study are primary data and secondary data. Primary data collection is done through direct interviews and recording (questionnaire). Secondary data was taken from agencies related to this research. There are two data analysis methods used, namely descriptive qualitative and descriptive quantitative. The results showed that 94% of farmers were male, the average age of farmers was 40-49 years by 42%, the farmer's education was relatively low, namely elementary school graduates by 39%, the number of household members ranged from 4-6 people by 61% , experience in paddy rice farming on average 11-20 years is 30%, the average farmer's land area of ​​91% only cultivates rice farming under 0.9 hectares, land cultivation status of 51% is owner-cultivator farmers. The net income obtained by the 33 sample farmers is Rp. 48,928,500 with an average net income of Rp. 1,482,682. With a large R/C ratio of (> 1), it means that rice farming in Nagari Pematang Panjang, Sijunjung District, Sijunjung Regency is feasible to continue.